UMP Kinase Regulates Chloroplast Development and Cold Response in Rice - Dong, Qing; Zhang, Ying-Xin; Zhou, Quan; Liu, Qun-En; Chen, Dai-Bo; Wang, Hong; Cheng, Shi-Hua; Cao, Li-Yong; Shen, Xi-Hong (International journal of molecular sciences, 2019)
Pyrimidine nucleotides are important metabolites that are building blocks of nucleic acids, which participate in various aspects of plant development. Only a few genes involved in pyrimidine metabolism have been identified in rice and the majority of their functions remain unclear. In this study, we used a map-based cloning strategy to isolate a UMPK gene in rice, encoding the UMP kinase that phosphorylates UMP to form UDP, from a recessive mutant with pale-green leaves. In the mutant, UDP content always decreased, while UTP content fluctuated with the development of leaves. Mutation of UMPK reduced chlorophyll contents and decreased photosynthetic capacity. In the mutant, transcription of plastid-encoded RNA polymerase-dependent genes, including psaA, psbB, psbC and petB, was significantly reduced, whereas transcription of nuclear-encoded RNA polymerase-dependent genes, including rpoA, rpoB, rpoC1, and rpl23, was elevated. The expression of UMPK was significantly induced by various stresses, including cold, heat, and drought. Increased sensitivity to cold stress was observed in the mutant, based on the survival rate and malondialdehyde content. High accumulation of hydrogen peroxide was found in the mutant, which was enhanced by cold treatment. Our results indicate that the UMP kinase gene plays important roles in regulating chloroplast development and stress response in rice.